In situ functionalization of a cellulosic-based activated carbon with magnetic iron oxides for the removal of carbamazepine from wastewater - Pereira, Diogo (2021)
The main goal of this work was to produce an easily recoverable waste-based magnetic activated carbon (MAC) for an efficient removal of the antiepileptic pharmaceutical carbamazepine (CBZ) from wastewater. For this purpose, the synthesis procedure was optimized and a material (MAC4) providing immediate recuperation from solution, remarkable adsorptive performance and relevant properties (specific surface area of 551 m2 g-1 and saturation magnetization of 39.84 emu g-1) was selected for further CBZ kinetic and equilibrium adsorption studies. MAC4 presented fast CBZ adsorption rates and short equilibrium times (< 30-45 min) in both ultrapure water and wastewater. Equilibrium studies showed that MAC4 attained maximum adsorption capacities (qm) of 68 ± 4 mg g-1 in ultrapure water and 60 ± 3 mg g-1 in wastewater, suggesting no significant interference of the aqueous matrix in the adsorption process. Overall, this work provides evidence of potential application of a waste-based MAC in the tertiary treatment of wastewaters.